A study of perceived facilitators to physical activity in neurological conditions - Elsworth, C; Dawes, H; Sackley, C; Soundy, A; Howells, K; Wade, D; Hilton-Jones, D; Freebody, J; Izadi, H (MA Healthcare Ltd, 2009)
Aims: The study aimed to determine the opinions of individuals with neurological conditions on factors facilitating their physical activity participation.